IBM z/OS V2R2 user interfaces - Winnard, Keith; Hering, Paul-Robert (IBM Corporation, International Technical Support Organization, 2015)
This IBM® Redbooks® publication helps you to become familiar with the technical changes that were introduced into the User Interface areas of IBM z/OS® V2R2. This publication is one in a series of IBM Redbooks publications that take a modular approach to providing information about the updates within z/OS V2R2. This approach has the following goals: - Provide modular content - Group the technical changes into a topic - Provide a more streamlined way of finding relevant information that is based on the topic It is our hope that this approach is useful. We value your feedback.
Number on resource description page: SG24831100. - "z Systems.". - Includes bibliographical references. - Description based on online resource; title from cover page (Safari, viewed January 21, 2016)
Keywords: z/OS; User interfaces (Computer systems); Database management; User-Computer Interface; Interfaces utilisateurs (Informatique); Bases de données; Gestion